Impact of Preparation Method in Co-Amorphous System (Sciences of Pharmacy, 2022)
The co-amorphous solid dispersion system is one of the methods to improve the physicochemical characteristics and stability of a drug. With the appropriate material ratio and preparation method, a co-amorphous solid dispersion system can increase the bioavailability of the drug due to an increase in solubility. In addition, the co-amorphous system will maintain its amorphous shape longer than a single compound. However, using unsuitable materials and methods for co-amorphous fabrication will precipitate them and diminish their bioavailability. As a result, exploring the fundamentals of co-amorphous manufacturing methods is essential. This article discusses the physicochemical properties and solubility of co-amorphous mixtures prepared by solvent evaporation, milling, and quenching methods. Scopus, PubMed, and Google Scholar literature were obtained using the keywords 'co-amorphous preparation', 'co-amorphous method', 'solvent evaporation for co-amorphous preparation', 'milling methods for co-amorphous preparation', and 'quenching method for co-amorphous preparation'. We excluded literature whose application was not in the medical field. Based on the findings, the co-amorphous preparation methods have their respective advantages and disadvantages. Solvent evaporation can only be used on a small scale. Milling techniques are laborious and time-consuming but have a large yield and less chemical destruction, while the quenching method is only intended for thermostable compounds.